μ-Opioid Receptor Cell Surface Expression Is Regulated by Its Direct Interaction with Ribophorin I - Ge, Xin (American Society for Pharmacology and Experimental Therapeutics, 2009)
The trafficking of the μ-opioid receptor (MOR), a member of the rhodopsin G protein-coupled receptor (GPCR) family, can be regulated by interaction with multiple cellular proteins. To determine the proteins involved in receptor trafficking, using the targeted proteomic approach and mass spectrometry analysis, we have identified that Ribophorin I (RPNI), a component of the oligosaccharide transferase complex, could directly interact with MOR. RPNI can be shown to participate in MOR export by the intracellular retention of the receptor after small interfering RNA knockdown of endogenous RPNI. Overexpression of RPNI rescued the surface expression of the MOR 344KFCTR348 deletion mutant independent of calnexin. Furthermore, RPNI regulation of MOR trafficking is dependent on the glycosylation state of the receptor, as reflected by the inability of overexpression of RPNI to affect the trafficking of the N-glycosylation-deficient mutants, or GPCRs that have minimal glycosylation sites. Hence, this novel RPNI chaperone activity is a consequence of N-glycosylation-dependent direct interaction with MOR.